Specifics of decision making in modern business systems : regularities and tendencies - Popkova, Elena G.,; Chesnokova, Alina V.,; Morozova, Irina A., (Emerald Publishing Limited, 2019)
Under the increasing influence of globalization, integration and technological progress, modern business systems have become highly complex in terms of their organization, strategies and management. Specifics of Decision Making in Modern Business Systems: Regularities and Tendencies concentrates on how this changing context of the modern business system affects the process of decision making within organizations and corporations.With a focus on the regularities and tendencies of decision making within modern Russian business systems, the numerous contributors provide alternative and innovative ways to optimize and develop the process of decision making within businesses globally. This includes the use of forecasting within the consumer market, a consideration of public-private partnerships, and the development of a cluster platform to unify large, medium and small businesses.Specifics of Decision Making in Modern Business Systems provides a useful insight into the optimization of decision making within businesses for researchers and practitioners working within information economy creation and development and management strategy.